Phenomenological Study of Teachers' and Early Childhood Children's Experiences in Learning through the Joyful Learning Approach at PAUD Hatuhuran, Kairatu District, West Seram Regency - Halamury, Mercy Florence; Muliyani, Muliyani; Kakiay, Septianty; Kainama, Nacie (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to understand the experiences of teachers and early childhood in PAUD Hatuhuran, Kairatu District in learning through the Joyful Learning approach. Using a qualitative phenomenological approach, data were obtained through interviews, participant observations, and reflective notes on teachers and students. The results showed that the Joyful Learning method—which combines games, nature exploration, and arts and culture—successfully increased children's active involvement, curiosity, and social, emotional, and cognitive development. Children appeared more enthusiastic and active during the learning process. However, teachers face challenges in managing dynamic classes, limited facilities, and minimal parental support. Teachers are required to be creative and adaptive in designing learning activities that are fun but still educational. This study emphasizes the importance of the role of teachers in creating meaningful learning experiences through a child-centered approach.